Gwary Lubelszczyzny w ujęciu Władysława Kuraszkiewicza - Pelcowa, Halina (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2018)
The article is concerned with the state of the Lublin region dialects from the first half of the 20th century and their description made by Władysław Kuraszkiewicz in the monograph Dialectology. The overview of the dialects of the Lublin region from 1932. Kuraszkiewicz’s account has been confronted with later research and today’s state of dialectal diversification of the Lublin region. The multifaceted character of the linguistic analyses included in the monograph has been pointed out as well as the fact that they perform an important function in current dialectal research. They are still a source of inspiration and discovery of the ethnically, culturally and ethnographically complex linguistic diversification of the Lublin region.